Investigation of Sediment Layer Thickness Estimation at Bengkulu University Hospital Based on Microtremor Data - Al Ansory, Andre Rahmat; Raihana, Hana; Farid, M; Hadi, Arif Ismul (JURNAL GEOCELEBES, 2024)
Bengkulu is the capital of Bengkulu Province and is located in the subduction zone between the Eurasian and Indo-Australian plates. Bengkulu is also close to the major faults of Sumatra, namely the Musi fault, the Ketahun fault, and the Manna fault. Therefore, regional planning and infrastructure development for earthquake mitigation is necessary. The purpose of this study is to estimate the thickness of the sedimentary layers in the construction zone of Bengkulu Hospital during the earthquake attenuation phase. This study is conducted by surface geological analysis using the HVSR method; data analysis using microtremor data. The microtremor data were analyzed using the HVSR method to obtain the amplification value (A0) and the dominant frequency (f0). HVSR analysis gave dominant frequency (f0) values from 5.1 to 5.8 Hz, amplification (A0) from 1.64 to 5.91 times, and dominant period (T0) from 1.49 to 2.81 seconds. The values of A0, f0, T0 are interpreted with reference to the literature and surface geology as a moderate risk of seismic vulnerability, characterized by moderate to weak sedimentation and moderate amplification values.